Correlation between the results of cultures and the molecular BIOFIRE® joint infection panel in a cohort of pediatric patients with bone and joint infections in Bogotá, Colombia - Camacho-Moreno, Germán; Vergara-Amador, Enrique; Martínez-Villegas, Tomás; Aragón-Joya, Yefry; Romero-Cardozo, Luz; Lores-Garcia, Francisco; Moreno, Vivian Marcela; Leal-Castro, Aura Lucia (Frontiers in Pediatrics, 2024)
Introduction. Bone and Joint Infections(BJI) have high morbidity. Methicillin resistant Staphylococcus aureus(MRSA) has increased. Culture-based diagnosis has difficult to recovering fastidious bacteria and detecting polymicrobial infections, molecular methods offer a promising improvement for the diagnosis of BJI with reduced time to result. The aim of the study was to determine the correlation between culture results and the Biofire joint infection panel(BJIP) in a cohort of pediatric patients with BJI. Materials and methods. Descriptive study. Patients admitted with probable o confirmed BJI between July 1, 2019 and February 28, 2021 at HOMI. Blood cultures, synovial and bone fluid samples were taken. Samples were kept at -70°C. On September 2022, the panel was performed. Results. 32 patients were included. The average age was 83m(RIQ:32-145). 23(71.8%) patients had a positive culture. The most frequent microorganism were S.aureus 19(83%), 11/19(57.9%) Staphylococci isolates were MRSA. 24/32(75%) were positive by panel, 20 positive detections were concordant with culture, there were 6 additional isolates by panel(2 S.aureus, 2 S.pyogenes, 1 K.kingae and 1 C.albicans), three microorganisms were isolated in culture but not in the panel. (2 S.aureus and 1 S.agalactiae). Two patients with coinfection were detected. All MRSA were detected by culture and panel. In 26(81.3%) patients the etiology was documented by any method. Conclusion: These results showed a moderate level of agreement between BJIP and culture(kappa=0.47). The panel allowed the detection of fastidious bacteria including K.kingae and polymicrobial samples. There was a very good level of agreement between the panel and culture for the MRSA detection(Kappa=1).